Awareness about health insurance in rural population of South India - Gowda, Sudhir; Manjunath, Chaitra; Krishna, Deepa (International Journal Of Community Medicine And Public Health, 2017)
Background: In India, despite improvements in access to health care, social inequalities are gross in both rural and urban areas. Many middle and lower socio economic class families are crushed under debts at the time of hospitalization due to lack of health insurance. Health financing is an important part of broader efforts to ensure social protection in health. However “health insurance” is still an unknown word for most rural people. So this study was undertaken with the objective to assess the awareness about Health Insurance in rural areas and to describe the sociodemographic characteristic of respondents. Methods: A cross sectional community based study was done with sample size of 290 households estimated by using 25% national coverage according to Public Health Foundation of India. The study was conducted between July 2014 to August 2014. 290 families were covered from two Primary Health Centres which come under field practice area of our medical college. A pretested semi structured questionnaire was used to collect data. Data was entered in excel sheet and analysed using SPSS version 17 software. Results:Among 290 respondents 72.5% were in age group of 26-45 years, 69.4% were female, 82.1% belonged to below poverty line, 72.4% were from nuclear family and about 81% of respondents were aware of Health Insurance. Conclusions:Awareness about Health Insurance among rural population was satisfactory. Attention for implementation of health insurance policies has to be paid more importance than only awareness.